Pengembangan Aplikasi Bank Darah Pada Palang Merah Indonesia(PMI) Jakarta Barat Berbasis Web - Yunita Sartika Sari; Irma Hamidah Nasution (Fakultas Ilmu Komputer, 2020)
The blood bank application is a website-based application that is used to manage blood stock supplies and provide information related to blood donor raising schedules. Blood banking is a process to ensure that donated blood is safe and in accordance with medical procedures. The Indonesian Red Cross (PMI) is an agency that manages blood transfusions and donors throughout Indonesia. The existence of PMI is very much needed by the community, especially in the need for blood stocks when in an emergency situation and requires blood transfusions. For this reason, an application is needed that can assist in the process of blood donation activities. The analytical method used is the PIECES method (Performance, Information, Economics, Control, Efficiency, and Service) and the system development method using the prototype method. The results of the development of this system are optimizing the process of managing blood stocks and information related to the schedule for raising blood donors, as well as improving the performance of officers in managing blood bank data. Keywords: Application, Website, Blood Bank, Blood Donor, PMIABSTRAK Aplikasi Bank darah adalah aplikasi berbasis website yang digunakan untuk mengelola persediaan stok darah dan memberikan informasi yang terkait dengan jadwal penggalangan donor darah. Bank darah merupakan proses untuk memastikan bahwa darah yang disumbangkan aman dan sesuai dengan prosedur medis. Palang Merah Indonesia(PMI) merupakan instansi yang mengelola transfusi dan donor darah diseluruh Indonesia. Keberadaan PMI sangat dibutuhkan oleh masyarakat, terutama dalam kebutuhan stok darah ketika dalam keadaan gawat darurat dan membutuhkan transfuse darah. Untuk itu, diperlukannya aplikasi yang dapat membantu dalam proses kegiatan donor darah. Metode Analisa yang digunakan adalah metode PIECES(Performance, Information, Economics, Control, Efficiency, and Service) dan metode pengembangan system menggunakan metode prototype. Hasil dari pengembangan sistem ini yaitu mengoptimalkan proses pengelolaan stok darah dan informasi yang terkait dengan jadwal penggalangan donor darah, serta dapat meningkatkan kinerja petugas dalam mengelola data bank darah. Kata kunci: Aplikasi, Website, Bank darah, Donor darah, PMI